Graphene Nanoribbon Simulator of Vacancy Defects On Electronic Structure - Kien Liong Wong; Mohamad Azri Sufi Mahadzir; Wee Khang Chong; Mohd Shahrizal Rusli; Cheng Siong Lim; Michael Loong Peng Tan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
Graphene Nanoribbon Simulator (GNRSIM) is developed using MATLAB Graphical User Interface Development Environment to study the electronics properties of graphene nanoribbons (GNRs). The main focus of this research is the simulation effects of single vacancy 1 in graphene nanoribbons lattices on electronic structure. The band structure and density of states are explored by using tight binding approximation where a Hamiltonian operator with nearest-neighbor interactions is introduced. The simulator has a wide range of input parameters where user can select armchair or zigzag GNR. The size of the lattices namely width and length can be varied. The location of the vacancy defect can be pinpoint by providing the row and column of the missing atom. The limitation of GNRSIM at present is that it can only accept a single atom vacancy. GNRSIM is able to be executed as a standalone application software in understanding the fundamental properties of semiconductor material and device engineering through ab-initio calculations.